Methods for Providing a System of Care for an Oxazaphosphorine Drug Regimen - O'DONNELL, JR. FRANCIS; SANTOS CARLOS (2011)
The present invention provides methods of treating subjects with an oxazaphosphorines, methods of identifying subjects that are suitable for oxazaphosphorine treatment, and systems for ensuring the safety and efficacy of a treatment that includes oxazaphosphorine administration.